Eggs of Thamnodontus Kluge, 2004 (Ephemeroptera: Heptageniidae: Ecdyonurinae): an additional diagnosis of the genus - Tiunova, Tatiana M. (Zootaxa, 2026)
Eggs of mayflies of the genus Thamnodontus Kluge, 2004 were examined using a scanning electron microscope. The structure of eggs of all three known species of the genus is described for the first time: T. aurarius (Kluge, 1983), T. dracon (Kluge, 1983), and T. tobiironis (Takahashi, 1929). Additional drawings and descriptions of male genitalia are also provided for these species. The egg chorionic structure of the genus Thamnodontus, together with other morphological characters, is useful for generic identification. A key to known eggs of the subfamily Ecdyonurinae is provided.